2015
DOI: 10.1186/s13054-015-1142-z
|View full text |Cite
|
Sign up to set email alerts
|

Combining multiple ECG features does not improve prediction of defibrillation outcome compared to single features in a large population of out-of-hospital cardiac arrests

Abstract: IntroductionQuantitative electrocardiographic (ECG) waveform analysis provides a noninvasive reflection of the metabolic milieu of the myocardium during resuscitation and is a potentially useful tool to optimize the defibrillation strategy. However, whether combining multiple ECG features can improve the capability of defibrillation outcome prediction in comparison to single feature analysis is still uncertain.MethodsA total of 3828 defibrillations from 1617 patients who experienced out-of-hospital cardiac arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
0
19
1
1
Order By: Relevance
“…Special focus has been put on the thorough characterization and parametrization of the entropy measures. Four of the six analyzed features were conveniently adapted to encompass VF amplitude information and were shown to be at least as effective in shock outcome prediction as the most elaborate predictors described to date [23,25,26]. This indicates that quantitative entropy measures may be an adequate tool to characterize the non-linear dynamics of the VF waveform.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Special focus has been put on the thorough characterization and parametrization of the entropy measures. Four of the six analyzed features were conveniently adapted to encompass VF amplitude information and were shown to be at least as effective in shock outcome prediction as the most elaborate predictors described to date [23,25,26]. This indicates that quantitative entropy measures may be an adequate tool to characterize the non-linear dynamics of the VF waveform.…”
Section: Discussionmentioning
confidence: 92%
“…As shown in Table 3, the BER for the best entropy predictor (FuzzEn) was 2.4 points higher than that of the best classical predictor (MSI), which means a combined increase of around five points in SE and SP. There is currently contradictory evidence on the benefits of combining features for shock outcome prediction, with studies showing increases of up to six points in BER for combinations of 3-10 features [57,58] and studies showing no increase in accuracy [23,26]. In a recent study with a large cohort of 1617 patients and 3828 shocks, He et al [26] found no benefits in combining features and showed the strong correlation among features, such as MdS, AMSA, PPA or energy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations